SAFE THRESHOLDS FOR THE PARAMETERS OF CRYPTOGRAPHIC ALGORITHMS AND STANDARD ST RK 1073-2007 - Abdrakhmanov, A.E.; Turdiyeva, G.T. (Academic Scientific Journal of Computer Science, 2020)
This article considers the problems of finding modern secure thresholds for the parameters of cryptographic algorithms. We conducted a comparative analysis of the obtained secure thresholds against the thresholds of the state standard of the Republic of Kazakhstan ST RK 1073-2007 "Means of cryptographic protection of information. General technical requirements." Based on the results of the analysis and taking into account the experience of certification tests, we worked out specific proposals for amendments and additions to this Standard.